Optimal design of a base isolated system for a high rise steel structure. - Kaplan, H.
In a previous study, the authors proposed a base isolation system for earthquake protection of structures. The system incorporates spherical supports for the base, a specially designed spring cam system to keep the base rigidly supported under normal conditions and to allow it to move for the duration of the earthquake under the constraint of a spring with optimized stiffness characteristics. A single degree of freedom structure was considered to investigate the feasibility of the concept. The simulation of the system response shows 20 times reduction of the transmitted force as a result of using the proposed design in the considered case. This paper extends the previous study to the case of a 40 storey steel structure subjected to the Taft as well as El Centro earthquakes. A 7.5 and 6 times reduction of the maximum transmitted force was achieved for the considered disturbances, respectively, without any adverse effects due to the tilting moment which is inherent in this type of base isolation.
Keywords: Base isolated system; High rise steel structure